Workshop and Education on Making Hand Sanitizer, Handsoap, and Disinfectant Products as Steps to Prevent the Spread of Covid-19 - Siti Zulaicha, Annisaa; Puspitasari, Indah; Saputra Yasira, Angga; Syahjoko, Iwan; Ghifari, M Alvien (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2021)
Hand sanitizers, handsoaps, and disinfectants (H2D) have become necessities in a new normal during the Covid-19 pandemic. These three items are necessary to use in daily activities to prevent the spread of Covid-19. One of the efforts to successfully adopt a new normal is to educate the youth on preventing the spread of Covid-19. Workshop and education on making simple H2D at SMK Negeri 3 Kotabumi have been held through outreach activities and hands-on practice. The goal of this activity is to increase the students knowledge of SMK Negeri 3 Kotabumi in living a new lifestyle to prevent the spread of Covid-19 in North Lampung Regency. The result of this educational program is an increase in the knowledge of students of SMK Negeri 3 Kotabumi about H2D in terms of composition, making, and use. Besides, through the workshop program, students of SMK Negeri 3 Kotabumi also acquire skills in making simple H2D. Through presentation and direct practice, students of SMK Negeri 3 Kotabumi have been educated to become new lifestyle agents to prevent the spread of Covid-19 in North Lampung Regency.